Transeuropski željeznički projekt - Mađarić, Juraj; Mlinarić, Tomislav (Promet - Traffic&Transportation, 2012)
Since the month of August 1992 an agreement has been available for signing based upon which the governments of the European countries participating in TER Project accept the obligation of instituting a fund to secure the sources for financing the completion of one of the most significant multi- national projects in Eastern Europe. For Croatia this assumes particular meaning because the project anticipates including our railway line from Botovo via Zagreb and Rijeka to Trieste as making part of a future main railway link from Kiev via Budapest, Zagreb, Rijeka, Trieste, Venice all the way to Barcelona.